Specimen Preparation and Experimental Setup. - Na Zhao (112953) (2025)
Rock defects are a key internal factor leading to deformation and failure under load. This study investigates red sandstone specimens with combined pore–fracture defects at different pore dip angles through uniaxial compression tests, while employing Acoustic Emission monitoring to capture the failure process. The evolution of AE characteristic parameters and rock failure modes is analyzed. The results indicate that: (1) the presence of pores prolongs both the time to failure and the onset of the AE burst stage, with longer durations observed at higher pore dip angles; (2) AE signal amplitude and frequency vary significantly across different loading stages, and the b-value exhibits an “increase–fluctuation–decrease” trend, with the decreasing stage serving as a precursor to rock instability; (3) pore dip angle strongly influences crack propagation types: dip angles of 0°–30° favor axial cracks and through-going wing cracks, 45°–75° angles tend to induce co-planar and wing crack connectivity, while 90° angles cause crack deviation, hindering through-going failure; (4) intact rock fails in a tensile–shear mixed mode, whereas the number of shear cracks in rocks with pores initially increases and then decreases with dip angle, reaching a maximum at 45°, resulting in shear-dominated failure. These findings reveal the failure characteristics and AE evolution patterns of rocks with combined pore–fracture defects at different pore dip angles, providing insights for the identification of precursors to rock failure and for disaster prevention and mitigation.